Detection of moisture content in transformer oil using platinum coated on D-shaped optical fiber - Yusoff, Siti Fatimah Az Zahra; Mezher, M.H.; Amiri, Iraj Sadegh; Ayyanar, Natesan; Vigneswaran, Dhasarathan; Ahmad, Harith; Zakaria, Rozalina (Elsevier, 2018)
The presence of moistures in transformer deteriorates transformer insulation. These effects decrease both electrical and mechanical strength of the transformer. Water in transformer oil also brings the risk of bubble formation when desorption of water increases the local concentration of gases in the oil. The water content in the insulating oil (or transformer oil) needs to be less than 10 ppm at normal temperature or contradictory, it will affect the efficiency of the power transformer system. Here, we report a D-shaped optical fiber sensor coated with a platinum thin layer with a thickness of 25 nm was designed to detect the response of transverse electric field (TE) power towards the content of moisture in the insulating oil. A Simulative based investigation using COMSOL Multiphysics has also been carried out to study the relation between analyte on the materials at different refractive index and the simulation study follows the finite element method (FEM). Four samples of aged oil were tested from actual transformer oil with different values of water contents of 15 ppm, 16 ppm, 18 ppm, and 21 ppm. The oil samples were dropped on the sensing region of the fiber and resulting in the drop of TE power from the initial value. It was observed that higher values of water percentages in the oil caused large fluctuations in TE power. On top of that, the changes in TE power show that the sensor is having fast response and good sensitivity.